2014
DOI: 10.1002/ptr.5207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smilaxchinoside A and Smilaxchinoside C, Two Steroidal Glycosides from Smilax riparia, on Hyperuricemia in a Mouse Model

Abstract: The roots and rhizomes of Smilax riparia, called 'Niu-Wei-Cai' in traditional Chinese medicine, are believed to be effective in treating the symptoms of gout. However, the active constituents and their uricosuric mechanisms are unknown. In this study, we isolated two steroidal glycosides, named smilaxchinoside A and smilaxchinoside C, from the total saponins obtained from the ethanol extract of the roots of S. riparia. We then examined if these two compounds were effective in reducing serum uric acid levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Sugar part in their structure plays an important role in XOD inhibition due to only sugar difference ilexsaponin C and prosapogenin possessed higher XOD inhibitory activities in contrast to other saponins. Smilaxchinoside A and smilaxchinoside C from Smilax riparia also possessed strong XOD inhibitory activities (Wu, Wang, et al., ). In another study, a saponin glycoside Pallidifloside D also showed potency toward XOD from roots and rhizomes of S. riparia (Wu, Ruan, Zhang, Wang, & Zhang, ).…”
Section: Natural Compounds: As a Xanthine Oxidase Inhibitorsmentioning
confidence: 99%
“…Sugar part in their structure plays an important role in XOD inhibition due to only sugar difference ilexsaponin C and prosapogenin possessed higher XOD inhibitory activities in contrast to other saponins. Smilaxchinoside A and smilaxchinoside C from Smilax riparia also possessed strong XOD inhibitory activities (Wu, Wang, et al., ). In another study, a saponin glycoside Pallidifloside D also showed potency toward XOD from roots and rhizomes of S. riparia (Wu, Ruan, Zhang, Wang, & Zhang, ).…”
Section: Natural Compounds: As a Xanthine Oxidase Inhibitorsmentioning
confidence: 99%
“…The sugar part in their structure has an important role in XO inhibition since it's the only difference between ilexsaponin C and prosapogenin and the latter possessed higher XO inhibitory activities compared to other saponins [63]. Smilaxchinoside A and smilaxchinoside C from Smilax riparia also had powerful XO inhibitory activities [64]. In another investigation, a saponin glycoside (pallidifloside D) extracted from roots and rhizomes of Smilax riparia, showed potent inhibition toward XO [65].…”
Section: Saponinsmentioning
confidence: 98%
“…The total saponins of this herb were for first time ever, shown to exhibit potent uricosuric activities in mice with hyperuricemia by downregulating kidney mURAT1 [ 43 ]. Subsequently, in a second study [ 44 ], the researchers isolated two steroidal glycosides from the total saponins of Smilax riparia A. DC roots, named smilaxchinoside A and smilaxchinoside C. They found that these two constituents exhibit great uricosuric effects. Meanwhile, the inhibition of XOD and the reduction in renal mURAT1 were also observed, which led to an enhancement in uric acid excretion as well as a decrease in kidney dysfunction induced by hyperuricemia [ 44 ].…”
Section: Herbs That Reduce Uric Acid By Inhibiting Its Production and Enhancing Its Excretionmentioning
confidence: 99%
“…Subsequently, in a second study [ 44 ], the researchers isolated two steroidal glycosides from the total saponins of Smilax riparia A. DC roots, named smilaxchinoside A and smilaxchinoside C. They found that these two constituents exhibit great uricosuric effects. Meanwhile, the inhibition of XOD and the reduction in renal mURAT1 were also observed, which led to an enhancement in uric acid excretion as well as a decrease in kidney dysfunction induced by hyperuricemia [ 44 ]. In a third study [ 45 ], they found two other steroidal glycosides, named timosaponin J and riparoside B.…”
Section: Herbs That Reduce Uric Acid By Inhibiting Its Production and Enhancing Its Excretionmentioning
confidence: 99%